Companies And Responsibility: Scope - Casanova Claros, Mariela (2015)
Conflicts that arise in society for the actions of the companies in the development of its activities are of the most varied and we find that the law has its own limitations to rule or punish them being difficult to attribute responsibility to entities that lack of ‘consciousness’ as it happens with legal persons as opposed to natural persons. The purpose of this article is to review the concept of the company as a legal entity and the scope of its responsibility as a legal structure. To do this, we will review the concept of responsibility; their types as well as the way to ask them responsibility for conduct that should be sanctioned.